External auditory canal metastasis leading to peripheral facial paralysis as first manifestation of de novo stage IV invasive lobular carcinoma of the breast: a rare case report - Lluís Garulo, David; Alonso, Maitane; Rodríguez, Judith; Manent, Natalia; Gomà Gallego, Montse; Guerra Fernández, Esther; Sanjuan Garriga, Francesc Xavier; Gubern Prieto, Paula; Penella Prat, Anna; Salinas Huertas, Sira; Chivite Guillen, David; Pernas, Sonia; et al. (Frontiers in Audiology and Otology, 2024)
Facial nerve (FN) palsy, as a solitary symptom resulting from metastatic tumor is uncommon, and metastases to the external auditory canal (EAC) are even more infrequent. In this article, we report a unique case of the novo stage IV invasive lobular breast carcinoma (ILC) presenting as an EAC metastasis and leading to FN palsy as the first symptom, highlighting the importance of considering a broad differential diagnosis.